Alloantigen-induced, T-cell-dependent production of nitric oxide by macrophages infiltrating skin allografts in mice - Krulová, M; Zajícová, A; Fric, J; Holán, V (Transplant international, 2002)
The immunological rejection reaction occurring after organ or tissue transplantation is characterized by a strong infiltration of the graft by T cells and macrophages. Since the rejection reaction is highly specific, we tested the role of T cells in the activation of macrophages and in the induction of nitric oxide (NO) production during graft rejection. The rejection of both MHC and non-MHC antigen-disparate skin allografts was associated with a significantly increased production of NO in the graft. The kinetics of NO production after transplantation correlated with the rejection reaction and with the fate of the allograft. A significant reduction in NO production was found in immunologically hyporeactive mice treated with cyclosporine, and no specific production of NO was found in tolerated skin allografts from neonatally tolerant mice. The production of NO was completely suppressed in graft explants from mice with depleted CD4(+) cells, but remained at a normal level in skin allografts from mice treated with anti-CD8 monoclonal antibody. The treatment of recipients of fully allogeneic skin grafts with 2-amino-5,6-dihydro-6-methyl-4H-1,3-thiazine (AMT), a specific inhibitor of the inducible NO synthase, resulted in a significant prolongation of graft survival. The results thus show CD4(+) T-cell-dependent, alloantigen-induced production of NO by graft-infiltrating macrophages and the role of NO in the rejection reaction. We suggest that this pathway may represent one of the local effector mechanisms of graft rejection.
Keywords: Nitric Oxide Synthase Type II; sekvence nukleotidů; DNA primery; kokultivační techniky; T-Lymphocytes; transplantace kůže; Transplantation, Isogeneic; Lymphocyte Depletion; makrofágy; oxid dusnatý; polymerázová řetězová reakce s reverzní transkripcí; lymfocytární deplece; synthasa oxidu dusnatého; myši inbrední BALB C; Isoantigens; Reverse Transcriptase Polymerase Chain Reaction; zvířata; Nitric Oxide; myši; Nitric Oxide Synthase; Mice, Inbred DBA; myši inbrední C57BL; imunosupresivní léčba; časové faktory; Mice; Transplantation, Homologous; Coculture Techniques; Kinetics; Lymph Nodes; Mice, Inbred A; lymfatické uzliny; Base Sequence; synthasa oxidu dusnatého, typ II; myši inbrední DBA; Mice, Inbred C57BL; Immunosuppression Therapy; transplantace izogenní; DNA Primers; isoantigeny; Skin Transplantation; T-lymfocyty; Animals; Macrophages; homologní transplantace; Time Factors; kinetika; Mice, Inbred BALB C; myši inbrední A